2023
DOI: 10.3389/fphar.2023.1125642
|View full text |Cite
|
Sign up to set email alerts
|

Insights into bone morphogenetic proteins in cardiovascular diseases

Abstract: Bone morphogenetic proteins (BMPs) are secretory proteins belonging to the transforming growth factor-β (TGF-β) superfamily. These proteins play important roles in embryogenesis, bone morphogenesis, blood vessel remodeling and the development of various organs. In recent years, as research has progressed, BMPs have been found to be closely related to cardiovascular diseases, especially atherosclerosis, vascular calcification, cardiac remodeling, pulmonary arterial hypertension (PAH) and hereditary hemorrhagic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 256 publications
1
10
0
Order By: Relevance
“…This agrees with the experimentally observed function of BMP9, which is to preserve EC quiescence [117,95,119]. However, BMPR2 loss in PAECs reverses the effect of BMP9 [118,120].…”
Section: 31supporting
confidence: 91%
See 1 more Smart Citation
“…This agrees with the experimentally observed function of BMP9, which is to preserve EC quiescence [117,95,119]. However, BMPR2 loss in PAECs reverses the effect of BMP9 [118,120].…”
Section: 31supporting
confidence: 91%
“…Additionally, we performed a semantic radiate analysis with BMP2 as the source resulting in a significant association with bone mineralization and positive regulation of osteoblast proliferation (Table 1 row 18). Not all the effects of BMP2 signaling are beneficial for PH patients, as BMP2 signaling can induce vascular calcification greatly diminishing the therapeutic potential of BMP2 in the treatment of PH [116, 117, 118].…”
Section: Resultsmentioning
confidence: 99%
“…CRIM1 modulates activity of bone morphogenic proteins, members of the TGFβ superfamily that are known to play roles in cardiac development and disease pathophysiology in HF, pulmonary arterial hypertension, and atherosclerosis. 39 Both THBS2 and TIMP1 are critical regulators of tissue homeostasis with roles in ECM remodeling, angiogenesis, and cell growth/differentiation, and have been extensively implicated in HF pathogenesis, 40,41 including in recent plasma proteome studies. [42][43][44] Other proteome features of particularly high interest have been linked to migration of various immune cell subsets in tissue homeostasis-specifically DLL1 (a ligand of Notch receptors), ESAM (endothelial cell adhesion molecule), JAM2 (involved in cell migration), and LAYN (involved in focal adhesion).…”
Section: Cell Migration and Tissue Homeostasismentioning
confidence: 99%
“…Kielin/chordin‐like protein (KCP) is a secretory protein with 18 cysteine‐rich domains 4 . Previous studies have shown that KCP is an enhancer of bone morphogenetic proteins (BMP) signaling and suppressor of transforming growth factor β (TGF‐β) signaling, 4 which are both involved in the regulation of fibrosis and cardiac remodeling 5 . It has been reported that KCP promotes BMP7 binding to its receptor, increasing the phosphorylation of intracellular Smad1, thereby ameliorating renal fibrosis 6 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Previous studies have shown that KCP is an enhancer of bone morphogenetic proteins (BMP) signaling and suppressor of transforming growth factor β (TGF-β) signaling, 4 which are both involved in the regulation of fibrosis and cardiac remodeling. 5 It has been reported that KCP promotes BMP7 binding to its receptor, increasing the phosphorylation of intracellular Smad1, thereby ameliorating renal fibrosis. 6 Meanwhile, KCP can inhibit activin A and TGF-β1mediated signal transduction in a paracrine manner through Smad2/3 pathway in renal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%